Application of capillary index score in predicting three-month functional outcome after endovascular treatment for acute ischemic stroke in China. Issue 3 (June 2020) - Duan, Zhenhui; Huang, Xianjun; Gao, Jie; Hu, Ting; Liu, Xiaoyun; Xiao, Lulu; Huang, Feihong; Sun, Rui; Zhu, Wusheng; Zhou, Zhiming; Liu, Xinfeng
Background: Preoperative neuroimaging assessment of collateral circulation is important for selecting acute ischemic stroke patients who are appropriate for endovascular treatment. We sought to validate the capillary index score system in an Asian population and compare its ability in predicting clinical outcomes with the American Society of Interventional and Therapeutic Neuroradiology/Society of Interventional Radiology grading system. Methods: We continuously enrolled acute ischemic stroke patients from two neurological centers from March 2014 to March 2017. Multivariate analyses were performed to assess the capillary index score system with 90-day clinical outcome (modified Rankin scale score). The scoring systems were compared for predicting good (modified Rankin scale 0–2) and excellent (modified Rankin scale 0–1) functional outcomes using area under the receiver operating characteristic curves. Results: We identified 157 patients (median age, 65 years; 96 (61.1%) males), of whom 71 (45.2%) patients with 90-day good functional outcomes were selected. Capillary index score was independently associated with clinical outcome after endovascular treatment (OR 0.63; 95% CI 0.43–0.92; P  = 0.016) with its predictive ability for good functional outcome (area under the receiver operating characteristic curve 0.755). For excellent functional outcome, the capillary index score system was not inferior to the American Society of Interventional and Therapeutic Neuroradiology/Society of Interventional Radiology grading system (area under the receiver operating characteristic curve 0.748 versus 0.793, P  = 0.09). Conclusions: The capillary index score system is a potentially useful tool for predicting 90-day functional outcomes in acute ischemic stroke patients after endovascular treatment.